EDUCATION IN THE NEW ERA: CHALLENGES AND OPPORTUNITIES FROM CONTENT-BASED CURRICULUM TO COMPETENCE-BASED CURRICULUM IN KENYA. - Wekesa Jesse, Dr. Napwora; Joshua Olela, Ochieng (International Journal of Scientific Research and Management (IJSRM), 2022)
The fast and complex changing world coupled with dynamic technical advancements and great need for skilled manpower in the labour market within an ever-growing world economy has brought new challenges and requirements in the education sector (Owala, 2021 in Mulenga and Kabombwe, 2019).The role of education in many African countries after independence was to impart knowledge to their citizens to help them take up leadership roles and positions in various sectors in order to help in the running of their countries. For example, in Kenya, there have been major reforms in the education sector since independence. The education system was changed in 1964 to 7-4-2-3  to de-colonise education. In 1985, the 7-4-2-3 system was changed to 8-4-4 following the recommendations of the Mackay Commission  in order to prepare its graduands for self-reliance, but seemingly, it never accomplished its mandate (Cheptoo and Ramdas, 2020) and in 2017, the education system changed from 8-4-4 to 2-6-3-3-3, which is a Competence Based Curriculum (CBC). Owala (2021) states that Kenya implemented the Competency Based Curriculum (CBC) in 2017 to help her citizens obtain appropriate knowledge, skills, values and attitudes through education with a focus on providing learners with the ability to obtain, improve and use knowledge, values and attitudes which would then lead to the use of skills acquired (Mulenga and Kabombwe, 2019). Momanyi and Rop (2019) argue that change of the education system to CBC was after prospective employer questioned the skills and capacity of university graduates’ competency. They state that competency means the graduates have sufficient knowledge and skills to perform an activity or service to a degree of quality that is acceptable to the industry and the customer in a time within which a competent person at the level could be reasonably be expected to perform the task.